Exploration of GGTase-I substrate requirements. Part 1: Synthesis and biochemical evaluation of novel aryl-modified geranylgeranyl diphosphate analogs. Issue 15 (1st August 2016) - Temple, Kayla J.; Wright, Elia N.; Fierke, Carol A.; Gibbs, Richard A.
Graphical abstract: Abstract: Protein geranylgeranylation is a type of post-translational modification that aids in the localization of proteins to the plasma member where they elicit cellular signals. To better understand the isoprenoid requirements of GGTase-I, a series of aryl-modified geranylgeranyl diphosphate analogs were synthesized and screened against mammalian GGTase-I. Of our seven-member library of compounds, six analogs proved to be substrates of GGTase-I, with6d having a k rel  = 1.93 when compared to GGPP ( k rel  = 1.0).